(DOXYCYCLINE INDUCED ESOPHAGEAL ULCER) - Rauf SEZER; Güngör BOZTAŞ; Zeynel MUNGAN; Celal ULAŞOĞLU; Sabahhatin KAYMAKOĞLU; Sadakat ÖZDİL and Fatih BEŞIŞIK and A. Faruk AĞAN and Arif ACAR and Oktay YEĞİNSÜ and et al. (Turkish Journal of Gastroenterology, 2020)
-